Expressão, purificação e caracterização estrutural de proteínas codificadas por dois fitovírus - Regatieri, Livia José [UNESP] (2014)
The Cole latent virus is a plant virus which infects mainly the common cole. It is a member of Carlavirus genus, which contains viruses that infect several plant groups, including those of great economic importance worldwide, as potato, soy, peanut and corn. The Pepper ringspot virus was first described during the 60’s in Brazil. It is characterized as member of Tobravirus genus and it can damage to cultures as tomato and pepper. Until now, the viral life cycle is not completely elucidated. It is known that some viral proteins are essential for infection, including the capsid protein (CP), movement protein (MP) and helicase (HEL). Those proteins do not have the structure determined, yet. Therefore, this work aimed the structural study of the capsid protein of Cole latent virus (CP-CoLV); movement protein of Pepper ringspot virus (MPPepRSV) and a helicase fragment of Pepper ringspot virus (HEL-PepRSV). Expression vectors containing sequences of interest were transformed Tests for protein expression at 37°C resulted in formation of inclusion bodies for the three tested proteins. The proteins present in inclusion bodies were solubilized and purified under denaturing conditions. The purified proteins were refolding by dialysis and concentrated. After refolding CoLV-CP and MP-PepRSV were analyzed by circular dichroism to check its secondary structure content. This analysis confirmed the refolding efficiency. The CP-CoLV was also analyzed by Dynamic Light Scattering to estimate the size distribution of particle populations which are present in the solution. The data of the dynamic light scattering showed that the protein is stable and monodisperse. Thus, among the proteins studied, the CP-CoLV showed better conditions for crystallization trials. When expressed at 18°C, it was possible to obtain the CP -CoLV in its native state. The protein was purified under non-denaturing and analyzed by infra-red spectroscopy. Using homology molecular ...